The role of matrix metalloproteinase-2 in the culture media in embryo implantation rate in normogonadotrophic cases undergoing ICSI - Yasser Ibrahim Orief; Mohamed Mourad Alabd; Yasser Saad Alkasar; Amr Gamil Koritam; Akram Deghedy (Middle East Fertility Society Journal, 2013)
Objective: The aim of the study is to correlate the changes in the biochemical marker MMP-2 in the culture media with the outcome of normogonadotrophic cases undergoing ICSI. Methodology: A prospective study of infertile females was conducted in El-Shatby Maternity University Hospital between October 2011 and May 2012 utilizing a sample of 40 normogonadotrophic infertile women (22 females with unexplained infertility and 18 females with tubal factor infertility). Results: Clinical pregnancy was 57.5%; 15 out of the 22 females with unexplained infertility and 8 out of the 18 females with tubal factor infertility. There was no abortion, ectopic or chemical pregnancy. Ongoing pregnancy after 14 weeks of gestational age was 100%. Total (MMP-2) ranged between (4.1 and 21.1) and (3.5–37) ng/ml with the mean of (9.91 ± 5.48) and (13.91 ± 8.87) ng/ml for non pregnant and pregnant groups respectively. There were no statistical significant differences between the two groups regarding total MMP-2 (P = 0.055). The mean of MMP-2/embryo/h ranged between (0.05 ± 0.05) and (0.06 ± 0.08) ng/ml/embryo/h for non pregnant and pregnant groups respectively. There were no statistical significant differences between the two groups regarding MMP-2/embryo/h (P = 0.234). Conclusions: MMP-2 concentration in the culture media cannot be used as a biochemical marker for embryo selection or prediction of implantation in the normogonadotrophic cases undergoing ICSI. Recommendations: Results of the present study suggest searching for other markers in the culture media for better embryo selection and for prediction of implantation in the normogonadotrophic cases undergoing ICSI.